'Not a Sex Question'? The One Big Union and the Politics of Radical Manhood - McCallum, Todd (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 1998)
In March 1919, over 230 union delegates assembled at the Western Labor Conference in Calgary to chart a radical new direction for wage workers through the creation of a revolutionary industrial union centre, the One Big Union (OBU). This essay argues that the practices of the OBU's radical manhood, their particular sense of what it meant to be a union man, shaped the organization's structure and politics as well as the emergent culture which fostered such widespread working-class radicalism. Drawing upon already existing practices espoused by Canadian labourists and American Wobblies as well as fashioning new ones, OBU men distinguished radical manhood from both the class politics and the masculinities of male bosses and scabs. While the organization of working women was not seen as an important issue at the WLC, the upsurge in women's militancy during the labour revolt prompted OBU supporters to encourage these women to join their male comrades. At times, advocates of the One Big Union posed the questions of women's oppression and emancipation as crucial elements of the union's purpose; their infrequent ideological commitment, however, too often failed to translate into organizational gains for working-class women and the development of feminist practices within the union. In their challenge to the bourgeois order, OBU men created a program that, in the prevailing context of gender relations, meant that the One Big Union would bring about the transformation, but not the eradication, of men's power.